PENGEMBANGAN WISATA BERBASIS MASYARAKAT DI LOKASI WISATA PANTAI JAKAT KOTA BENGKULU - Hendra Felani; Teddy Surya Rahmadi (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2022)
Jakat Beach is one of the belle of tourism in Bengkulu City, this is due to the tourist location which is only one kilometer from the center of Bengkulu City and easy access to tourist sites. But of course in the development of tourist objects need the readiness of the community as managers of tourist objects. Community-based tourism development is one of the tourism concepts that is expected to optimize the benefits felt by the community. This study aims to analyze the readiness of the people of Bengkulu City in developing community-based tourism objects in their area and realizing sustainable community-based tourism. This research was conducted using a qualitative approach by conducting interviews with the community and various stakeholders involved in the development effort. The analytical framework used to identify the condition of community readiness is the stages prepared by the Asia-Pacific Economy Cooperation (APEC). The results showed that the people of Bengkulu City had good readiness to be able to develop activities based on the 9 required stages, the people of Bengkulu City had reached the 7th stage. Therefore, the community needs to prepare several things so that tourism development can be sustainable. Keywords: Community Based Tourism, Jakat Beach